2016
DOI: 10.18632/oncotarget.7718
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of patient-derived xenograft models established from fine needle aspirate biopsies of a primary pancreatic ductal adenocarcinoma and from patient-matched metastatic sites

Abstract: N-of-1 trials target actionable mutations, yet such approaches do not test genomically-informed therapies in patient tumor models prior to patient treatment. To address this, we developed patient-derived xenograft (PDX) models from fine needle aspiration (FNA) biopsies (FNA-PDX) obtained from primary pancreatic ductal adenocarcinoma (PDAC) at the time of diagnosis. Here, we characterize PDX models established from one primary and two metastatic sites of one patient. We identified an activating KRAS G12R mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 58 publications
3
33
0
Order By: Relevance
“…BET bromodomains recruit CDK9, the catalytic subunit of P-TEFb, which catalyses the phosphorylation of serine 2 in the heptapeptide repeat sequence within the C-terminal domain of RNA polymerase II, a post-translational modification associated with transcriptional elongation 66. Importantly, Dinaciclib has been reported to abrogate PDAC growth and progression in vitro and in vivo69 70 and is currently being evaluated for its therapeutic potential in patients with PDAC in combination with the poly [ADP-ribose] polymerase (PARP) inhibitor veliparib (NCT01434316) and MK2206-mediated Akt inhibition (NCT01783171). Interestingly, CDK9 and BET inhibitors were also shown to function synergistically 71.…”
Section: Translational Approaches To Tackle Epigenetic Dysregulation mentioning
confidence: 99%
“…BET bromodomains recruit CDK9, the catalytic subunit of P-TEFb, which catalyses the phosphorylation of serine 2 in the heptapeptide repeat sequence within the C-terminal domain of RNA polymerase II, a post-translational modification associated with transcriptional elongation 66. Importantly, Dinaciclib has been reported to abrogate PDAC growth and progression in vitro and in vivo69 70 and is currently being evaluated for its therapeutic potential in patients with PDAC in combination with the poly [ADP-ribose] polymerase (PARP) inhibitor veliparib (NCT01434316) and MK2206-mediated Akt inhibition (NCT01783171). Interestingly, CDK9 and BET inhibitors were also shown to function synergistically 71.…”
Section: Translational Approaches To Tackle Epigenetic Dysregulation mentioning
confidence: 99%
“…46 More recently it has been shown that cfDNA also contains circulating tumor DNA that can contain mutations similar to those seen in a patient's tumor in xenograft models and in patient plasma samples. [46][47][48] One promising aspect of the liquid biopsy is in the use of blood testing to monitor patients with solid tumors for progression of disease and development of resistance as a complement to or replacement for additional imaging studies and tissue biopsy. 49,50 Clinical Challenges, Number of Genes, Number of Mutations, Reporting/Interpretation As a complex yet common disease, cancer causes enormous morbidity and mortality worldwide.…”
Section: Technical Issues To Consider For Implementing Somatic Mutatimentioning
confidence: 99%
“…We showed that deletion of CTK1 was synthetic lethal with loss of the yeast NF1 homolog IRA2. Furthermore, we have found that inhibitors of this process (dinaciclib, SNS-032) can inhibit other types of RASdysregulated tumor cells [9].…”
Section: Introductionmentioning
confidence: 99%